The Role Of Kaytsu and Cakradana In Promoting Trade In The Banten Sultanate In The 17th Century - Cesaria Oktaviani; Abd Rahman Hamid Rahman Hamid; Uswatun Hasanah Uswatun Hasanah (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2025)
This study aims to explain the role of Syahbandar Kyatsu and Cakradana in advancing trade in the Sultanate of Banten during the 17th century. Using historical research methods, including heuristics, source criticism, interpretation, and historiography, this study reveals that Syahbandar played a key role in the development of maritime trade. They introduced innovations in navigation systems, managed ports, and established regulations related to taxation and customs duties. In addition to being responsible for port administration and logistics, Syahbandar also acted as intermediaries between local and foreign traders, expanded global trade networks, assisted in contract negotiations, and facilitated the exchange of goods. With an in-depth understanding of both local and international markets, they directed trade flows towards the Sultanate of Banten and ensured the smooth distribution of goods. Indirectly, their role also contributed to the growth of the Muslim community in Banten. The implications of this study indicate that the role of Syahbandar not only impacted economic progress but also influenced the security system and stability of Banten's maritime territory in the 17th century.